DILEMA PREDESTINASI DALAM SIFAT ALLAH: “Kajian Terhadap Dilema Teologis Predestinasi Berdasarkan Sifat Sempurna Allah” - Pangeran Manurung; Esron Harianja (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2021)
The problem in this paper lies in the polemics that arise in the understanding of double predestination, especially regarding the theological dilemmas in it. On the one hand, God is portrayed as a cruel and inhumane God when only choosing some people to be saved, and on the other hand Christian doctrine admits that God does choose some people to love. The purpose of writing this essay is to prove that a comprehensive approach can reduce dilemmas and theological conflicts when discussing the formulation of predestination. The research method used is literature study, by describing the core of Calvin's dual predestination and reviewing it by involving the interrelated attributes of God. The results of this study prove that when the concept of predestination is reviewed by involving the attributes of God as a whole, it can be seen that God cannot be called an arrogant God when choosing humans in the project of salvation.